Eccentric hamstring strength in elite track and field athletes on the British Athletics world class performance program. (May 2020) - Giakoumis, Michael; Pollock, Noel; Mias, Eduard; McAleer, Stephen; Kelly, Shane; Brown, Freddie; Wootten, Moses; Macdonald, Ben
Abstract: Objectives: This novel study aims to provide unique data on eccentric hamstring strength in elite track and field athletes. Design: Clinical measurement, cross-sectional study. Setting: Across two British Athletics performance centres. Participants: 44 elite British track and field athletes. Main outcome measures: Eccentric hamstring force and torque were evaluated using the Nordbord device. Injury history and demographic data was collected to assess whether differences between gender, event group, limb symmetry and previous injury history were present. Results: Average peak force for males and females was 418.38N and 318.54N. Relative to body weight there were no gender differences (Male 5.21N.kg −1, Female 4.99N.kg −1 ) (p = 0.62). The right limb was significantly stronger in long sprint (400m athletes) (p = 0.00018) (d = 0.56). No differences in relative force or torque were observed between previously injured and non-injured limbs. Conclusions: This study provides unique data in elite track and field athletes. Relative force per kilogram should be used when comparing male and female athletes. Unlike other studies, we found no difference in eccentric strength between previously injured and non-injured limbs. The novel finding of increased eccentric strength demonstrated in the right limb in 400m sprinters may be due to the asymmetric demands of bend running and may be considered normal. Highlights: Asymmetry of eccentric hamstring strength may be a normal finding. No association between previous injury and hamstring strength. No gender difference in relative eccentric hamstring strength.